Making work work : the positivity solution for any work environment - Richards, Shola (Sterling Ethos, 2016)
"Making Work Work focuses on inspiring current and future leaders to start a movement that will banish on-the-job bullying, put meaning back into work, and enhance coworkers' happiness and engagement. Richards, whose popular blog has a worldwide following, explains why inaction is insane, why we must move forward with positivity, and why the "abc" employees (asshats, bullies, and complainers) are so destructive."--